KERJASAMA STAKEHOLDERS PEMERINTAH DESA DALAM MENDUKUNG DESA PELOPOR PEMBINA KETAHANAN PANGAN DI DESA KOTO TUO KECAMATAN KUANTAN HILIR KABUPATEN KUANTAN SINGINGI TAHUN 2018-2019 - Rahman, Purwanda; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The agricultural sector is one of the national development agendas in order to strengthen the resilience of the nation's economy. This is marked by the issuance of Law Number 41 of 2009 concerning Protection of Sustainable Food Agricultural Land. This sustainable agricultural sector can be said to be successful if the development of agricultural businesses, reliable and quality human resources and is supported by complete facilities and infrastructure can be fulfilled and run well. One of the villages in Kuantan Singingi Regency, Riau Province, namely Koto Tuo Village, has the potential for quite high agricultural products. This advantage should be a valuable asset to increase the diversity of people's food consumption. Koto Tuo Village is a village that is able to manage and utilize the wealth of its own village, besides that Koto Tuo Village has also distributed its agricultural products in Kuantan Singingi Regency. Although agricultural crops have varied, they are still dominated by rice.This study seeks to answer the researcher's questions as follows: How the Cooperation between the Stakeholders of Kuantan Hilir Subdistrict in Supporting Koto Tuo Village to Get the Adhikarya Pangan Nusantara Trophy at the Provincial Level, what are the supporting factors of the Koto Tuo village government in achieving Adhikarya Pangan Nusantara at the Provincial Level. This type of research used by the author in this study is descriptive. Data collection techniques are interviews, literature study and documentation. The data analysis technique in this study was carried out qualitatively.The results of the study explain that in achieving Adhykarya Pangan Nusantara's achievements, Koto Tuo Village requires collaboration between Village Government Stakeholders and guidance from the Village Head. In Cooperation, there is also a need to build partnerships, namely voluntary and cooperative relationships between several parties, both government and private, where everyone agrees to work together to achieve common goals and fulfill certain obligations and bear risks, responsibilities, resources, capabilities and benefits together.Keywords: Cooperation, Stakeholders, Village Government, and Development